Factors Influencing the Settlement of Domestic Transactions in Value Added Tax in Transport Companies - Owczarek, Ewelina (Journal of Finance and Financial Law, 2018)
This article was written in connection with many problems of taxpayers with the correct settlement of value added tax. These problems result, among other things, from the frequent changes in tax regulations, the continuous development of the transport industry in Poland and the expansion into foreign markets. The aim of the thesis is to identify the factors influencing the correctness of domestic settlements in value added tax for transport companies. The publication discusses the structural elements of the goods and services tax in Poland , characterizes the specificity of domestic settlements in VAT for transport companies and presents the procedure of domestic settlements in value added tax on the example of Transport Company XXX. The studies were carried out on the basis of the relevant documentation of all VAT transactions that took place in the above mentioned company in March 2017. The conducted research revealed a multitude of factors affecting the correct settlement of goods and services tax in companies providing domestic transport services. Their knowledge and proper application has a very large impact to correctly settle accounts with the Tax Office and keep tax books in accordance with the law